ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG BAHAN BAKAR MINYAK (BBM) BENSIN ECERAN DI KABUPATEN MERAUKE - Marthen Adrian Izak Nahumury; Agustinus Fangohoy (EKONOMI & SOSIAL, 2013)
This study aimed to determine the effect of income trader gasoline fuel dilution in this study merauke.Lokasi districts in Merauke regency in Papua province. This study uses a quantitative approach. The data used are primary data sourced directly from gasoline retailers Merauke district area and analyzed with qualitative analysis which is a referral from a reference quantitative analysis of the problem and analyze the factors that mempengharui income variation gasoline retailers using descriptive analysis through the analysis table. which is used as fuel gasoline retailers population of 15, whereas samples taken 10 gasoline fuel retailers. The results showed that the variation in the selling price and the level of gasoline dilution sitas real path to revenue berpengharuh gasoline fuel dilution in Merauke district